Desigualdade racial e educação: uma análise das políticas afirmativas no ensino superior - Ferreira, Nara Torrecilha (2017)
From the 2000s, affirmative policies began to be implemented in brazilian higher education, aiming to increase access to the black population at this level of education and the reduction of racial inequalities. The Law nº 12.711/2012 determined the adoption of national affirmative policy by all federal institutions of higher education as of 2013. The present work proposes the development of a reflection about these affirmative policies, aiming to elaborate a critical analysis in relation to their results. The fundamental question to be answered by this research is: Are the affirmative policies implemented in Brazilian public higher education helping to increase access to the black population? As auxiliary questions, this paper will attempt to answer the following questions: Are affirmative policies with only social criteria sufficient to increase access to the black population or are racial criteria necessary? Do the results vary according to the design of affirmative policies? Do the results vary by federation unit? The research used the tracing of affirmative policies implemented by higher education institutions, determined by state and municipal legislation, and by federal law, in order to identify the models of public policies adopted in the country. In addition, the research used the tracking of discussions in the press, using the newspaper Folha de S. Paulo, seeking to understand the environment for the elaboration and implementation of these policies, as well as to identify variables and hypotheses to be considered in the quantitative analysis. Finally, the study used correlation analyzes and multiple linear regression to evaluate the effectiveness of affirmative racial policies, considering the expansion of access to higher education to the black population.